Rehabilitation Issue of Stone Spouts as a Part of an Alternative Source of Public Water Supply Scheme Within Lalitpur Metropolitian City Area - Poudel, Govinda Prasad (Journal of Innovations in Engineering Education, 2020)
Stone spouts of LMC can be classified according to the water availability. Out of sixty-one stone spouts, only twelve numbers of stone spouts were effectively running up to 2006. These are Manga Hiti, Iku Hiti, Sincha Hiti, Haku Hiti, Konti Hiti, Alko Hiti, Chyasa Hiti, Sundhara, Tapa Hiti(a), Wasa Hiti, Tanga Hiti and Shova Hiti. These stone spouts are considered as good type according to availability of water. Remaining out of fourty- nine stone spouts thirty-four are less effective i.e average type and fifteen are dried up and not exist up to 2006. Comparing different scenarios and results from user’s survey in 2006 and 2019 it is found that yield capacity of every stone spout is being reduced every year and also dried up which we consider good type stone spouts like sundhara patan. Out of sixty-one stone spouts more than fourty stone spurts are almost dried up. This shows the immediate restoration requires for preservation of water from stone spouts.